An Assessment of Reading Competence in English of Entry Level Under-Graduate Students of Degree Colleges of Punjabi University, Patiala: Assessing Reading Competence in English of Undergraduate Students in Punjabi University, Patiala (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present paper aims to assess the existing level of reading competence in English of entry level under-graduate students of degree colleges affiliated with Punjabi University, Patiala (Punjab, India). It also aims to identify the strengths and weaknesses of the target students with regard to their reading skill. For this purpose, a comprehensive reading test (comprising three different tasks) was administered to 240 students selected as sample from eight colleges by using random sampling method. The responses of the test-takers were subjected to quantitative as well as qualitative assessment. The results obtained through quantitative analysis have been represented in the paper in form of tables and charts. In addition, a detailed discussion of the diagnostic inputs obtained through qualitative assessment of the responses of the test-takers has also been presented in the paper. Qualitative assessment of the responses was primarily carried out with an objective to identify those aspects of reading skill of the target students which they are most deficient in. A comprehensive assessment of the responses has led to an observation that despite undertaking a variety of reading during their school years, majority of target students only develop lexical and literal comprehension skills. Their interpretive and critical comprehension skills remain limited. They also appear to lack the subtle sub-skills of reading a factor which can be a considered responsible for their limited reading skills at advanced levels. Prior to representation and discussion of the results of quantitative and qualitative assessment, reading has been discussed as a skill along with various other concepts related to it in general and in the context of reading in English as a second language in particular.